2021
DOI: 10.3389/fpubh.2021.620264
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Healthcare Use in Older Adults: Evidence From a Nationally Representative Cohort in Northern Ireland—A Cross-Sectional Replication Study

Abstract: Background: Few have explored associations between loneliness and healthcare use independent of health and health behaviors. Recent indication of gender effects also requires validation across health service and cultural settings. We investigated the associations among loneliness, health and healthcare use (HCU) in older adults including stratification to investigate whether associations differed by gender.Methods: Secondary analysis of a nationally representative sample of 8,309 community-dwelling adults aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Journal of Community Psychology, 20(1), 43-56. https://doi.org/10.1002/1520-6629(199201)20:1<43::AID-JCOP2290200107>3.0.CO;2-3 Cohen-Mansfield, J., Hazan, H., Lerman, Y., & Shalom, V. (2016) Fair (Burns et al, 2020;2021;Ellaway et al, 1999;Houle et al, 2001) Three studies found loneliness associated with increased visits in previous year (Burns et al, 2020;Ellaway et al, 1999;Houle et al, 2001), one study also found this association for chronic loneliness (Burns et al, 2020) One study found no association between loneliness with number of visits in previous year (Burns et al, 2021) One study found no association between loneliness with the number of home visits from a GP in the previous 12 months ( Ellaway et al, 1999) Whether service used at all: cross-sectional 1 Self-reportprevious 12 months (Mosen et al, 2020) Single-item (Mosen et al, 2020) General population sample (Medicaid database)representative sampling (Mosen et al, 2020) Inadequate analysis (unadjusted Chi-Square analysis) (Mosen et al, 2020) Poor (Mosen et al, 2020) One study found that those people who were sometimes or often/always lonely were more likely to have visited primary care once or more in the previous year than those who were never lonely (Mosen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Journal of Community Psychology, 20(1), 43-56. https://doi.org/10.1002/1520-6629(199201)20:1<43::AID-JCOP2290200107>3.0.CO;2-3 Cohen-Mansfield, J., Hazan, H., Lerman, Y., & Shalom, V. (2016) Fair (Burns et al, 2020;2021;Ellaway et al, 1999;Houle et al, 2001) Three studies found loneliness associated with increased visits in previous year (Burns et al, 2020;Ellaway et al, 1999;Houle et al, 2001), one study also found this association for chronic loneliness (Burns et al, 2020) One study found no association between loneliness with number of visits in previous year (Burns et al, 2021) One study found no association between loneliness with the number of home visits from a GP in the previous 12 months ( Ellaway et al, 1999) Whether service used at all: cross-sectional 1 Self-reportprevious 12 months (Mosen et al, 2020) Single-item (Mosen et al, 2020) General population sample (Medicaid database)representative sampling (Mosen et al, 2020) Inadequate analysis (unadjusted Chi-Square analysis) (Mosen et al, 2020) Poor (Mosen et al, 2020) One study found that those people who were sometimes or often/always lonely were more likely to have visited primary care once or more in the previous year than those who were never lonely (Mosen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This association was not observed for people who were often lonely. Relationship between loneliness and healthcare utilization condition: longitudinal 9 years for CVD , falls , or respiratory disease 2020a; 2020b, 2020c) sampling (Bu et al, 2020a;2020b, 2020c confounder control (Bu et al, 2020a;2020b, 2020c 2020b, 2020c) adjusted risk of being hospitalised for CVD over follow-up One study found increasing levels of loneliness predicted an increased risk of being hospitalised due to falls, though this association was attenuated after adjustment for confounders One study found increasing levels of loneliness were not associated with the risk of hospitalisation due to respiratory disease over a median of 9 years (Bu et Two studies found non-significant adjusted associations (there were some significant unadjusted associations) between loneliness and emergency department visits over the previous 12 months robust to how loneliness was measured and gender stratification (Burns et al, 2020;Burns et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority emphasize that the somatision is a direct consequence of feeling neglected and lonely [70]. The need to communicate and fill the void of loneliness is evident on a physical level, and it is used as a way to connect with one's surroundings in an attempt to avoid one's soul becoming lonely [47,71,72]. Loneliness is self-reinforcing, leading to an even greater sense of isolation [27].…”
Section: Discussionmentioning
confidence: 99%